Injustice in dismissal : the anti-dismissal injunction - Kirwan, Brendan (Trinity College (Dublin, Ireland). School of Law, 2013)
The purpose of this research is to analyse, primarily by reference to the written judgments delivered in the Superior Courts, the development of the anti-dismissal injunction and associated complexities which can lead to a lack of coherent principles in the courts’ approach to such injunctions. This analysis can be divided into four sub-strands: (i) to consider the anti-dismissal injunction in the round and set out the basis for the courts’ approach to the remedy; (ii) to identify established principles which inform the granting or refusal of such injunctions; (iii) to identify where and why there is a lack of coherence and uncertainty in the courts’ approach to such injunctions; and (iv) to identify what might tentatively be called “starting points” for a reconsideration of how best the extraordinarily powerful remedy of the anti-dismissal injunction might be approached by the courts.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin